Vehicle and automotive engineering : proceedings of the JK2016, Miskolc, Hungary - Jármai, Károly; Bolló, Betti (Springer, 2017)
This book presents the proceedings of the first vehicle engineering and vehicle industry conference. It captures the outcome of theoretical and practical studies as well as the future development trends in a wide field of automotive research. The themes of the conference include design, manufacturing, economic and educational topics.
Keywords: Automobiles -- Design and construction -- Congresses.; Motor vehicles -- Design and construction -- Congresses.; Vehicles -- Design and construction -- Congresses.; elektronické knihy; electronic books